2021
DOI: 10.1371/journal.pgen.1009891
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of ASGR1 in pigs recapitulates reduced risk factor for cardiovascular disease in humans

Abstract: Genetic variants in the asialoglycoprotein receptor 1 (ASGR1) are associated with a reduced risk of cardiovascular disease (CVD) in humans. However, the underlying molecular mechanism remains elusive. Given the cardiovascular similarities between pigs and humans, we generated ASGR1-deficient pigs using the CRISPR/Cas9 system. These pigs show age-dependent low levels of non-HDL-C under standard diet. When received an atherogenic diet for 6 months, ASGR1-deficient pigs show lower levels of non-HDL-C and less ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Earlier studies have suggested that ASGR1 reduction increases LDLR and thus lowers blood cholesterol. For example, Xie et al 4 generated Asgr1 -deficient pigs and found that when fed a high-fat and high-cholesterol diet for 6 months, these knockout pigs had lower levels of non-HDL than control pigs. To determine the mechanism of action, Xie et al analyzed the hepatic transcriptomic profile and in vivo cholesterol metabolism and found that ASGR1 deficiency downregulated HMGCR but upregulated hepatic LDLR.…”
mentioning
confidence: 99%
“…Earlier studies have suggested that ASGR1 reduction increases LDLR and thus lowers blood cholesterol. For example, Xie et al 4 generated Asgr1 -deficient pigs and found that when fed a high-fat and high-cholesterol diet for 6 months, these knockout pigs had lower levels of non-HDL than control pigs. To determine the mechanism of action, Xie et al analyzed the hepatic transcriptomic profile and in vivo cholesterol metabolism and found that ASGR1 deficiency downregulated HMGCR but upregulated hepatic LDLR.…”
mentioning
confidence: 99%
“…Paris and his colleagues( Paris et al, 2011 ) knocked down ASGR1 to reduce ASGR1 expression in asynchronous primary enriched liver sinusoidal endothelial cells (eLSEC) and cripple the ability of primary porcine eLSEC to bind and phagocytose human platelets. Xie’s group( Xie et al, 2021 ) produced ASGR1-deficient pigs using the CRISPR/Cas9 system. The ASGR1-deficient pigs unexpectedly exhibited mild to moderate liver injury, which has not been reported in humans with ASGR1 variants.…”
Section: Advance Of Genetically Modified Pigs In Xenotransplantationmentioning
confidence: 99%
“…The development of high-precision genome editing tools, such as targeted nucleases, has accelerated advances in fundamental human medicine, animal science, animal breeding, as well as disease diagnosis ( Doudna and Charpentier, 2014 ; Kurtz et al, 2021 ; Rieblinger et al, 2021 ; Xie et al, 2021 ). In particular, the genome editing system known as CRISPR technology has grown rapidly since it was first reported ( Jinek et al, 2012 ) and has become one of the most popular technologies.…”
Section: Introductionmentioning
confidence: 99%